As práticas pedagógicas em um curso de pós-graduação em auditoria em sistemas de saúde em um centro educacional de Porto Alegre - Kessler, Cybele Chemale (Universidade do Vale do Rio dos Sinos, 2014)
The post graduation formation, lato sensu, is still a challenge in Brazil if pedagogical proposes that really foment reflections about taking actions to face the difficulties found in national health services are considered. The subject matter of Audit in Healthcare is also challenging whilst trying to breakthrough a traditional sense of this being a cost-cutting field. The objective of this research is to identify the main pedagogical practices applied on Audit in Healthcare Systems post graduation course from a Educational Centre located in Porto Alegre (RS). This is a descriptiveexploratory research using a qualitative approach. Data collections were done through semi structured interviews. Those interviews were recorded and lately transcripted, and all of them were previously scheduled and realized with the authorization of each interviewed person. Was used the content analysis of Minayo (2010). The application of groundbreaking methodologies in Audit teaching field helps to improve pedagogical proposes, enlightening the subject matter. The results found pointed to new five categories: auditing as surveillance action; the relation between costs and assistance quality; formation courses lato sensu; a necessity to integrate course’s disciplines; the diversity of pedagogical resources and the importance of practical activities; the challenge of evaluating teaching and learning processes; and the importance of teachers’ participation on the construction of course pedagogical project. This research enlights the importance of outlining strategies for education in Audit in Healthcare. A proper formation results in professionals ready to face the necessities of healthcare services associated to the necessities of pacients’ health. This essay points to the elaboration of a pedagogical matrix with orientations to help new teachers in their performance on Audit in Healthcare field.
Keywords: Auditoria; Saúde; Educação; Práticas pedagógicas; Audit; Health; Education; Pedagogical practices; ACCNPQ::Ciências da Saúde::Enfermagem